Ginsenosides Rg5 and Rk1, the skin-whitening agents in black ginseng. (June 2018) - Jin, Yan; Kim, Ji Hye; Hong, Hee-Do; Kwon, Jeonghun; Lee, Eun Jung; Jang, Mi; Lee, Sung-Young; Han, Ah-Ram; Nam, Tae Gyu; Hong, Seok Kyu; Huh, Tae-Lin; Kang, Nam Joo; et al.
Graphical abstract: Highlights: Inhibitory effect of black ginseng extract on melanin production on B16F10 and zebrafish model. Skin whitening activity of black ginseng extract on human skin. Ginsenoside Rg5 and Rk1, bioactive compounds in black ginseng extract for skin whitening activity. Activation MEK-ERK signaling pathway, a underlying mechanism for skin whitening activity of black ginseng extract. Abstract: Ginseng ( Panax ginseng Meyer) is widely used to treat various chronic disorders. Black ginseng is obtained by repeated steaming and drying of raw ginseng, which turn it black and convert the ginsenoside compounds present into more potent bioactive ingredients. The effects of a black ginseng extract on melanin production and skin whitening were evaluated in vitro as well as in vivo using human skin and zebrafish embryos. Tyrosinase activity decreased when steamed and dried ginseng was used. A pronounced skin-whitening effect was observed in our clinical study, and inhibition of melanin activity and tyrosinase levels was confirmed in zebrafish embryos. Two ginsenosides specific to black ginseng activate the MEK-ERK signaling pathway and are the main factors responsible for skin whitening. The skin-whitening effects of black ginseng are associated with the formation of two ginsenosides, indicating that black ginseng can be used as a novel skin-whitening agent in cosmetic products.